Peran Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Membaca Al-Qur’an pada Siswa Kelas III - Lufi Nur Shalma; Fitroh Hayati; Dewi Mulyani (UNISBA Press, 2022)
Abstract. The objectives of this study are 1) knowing how the role of Islamic Religious Education teachers in overcoming difficulties reading the Qur'an in grade III students at SDN 1 Kayuambon, 2) knowing the strategies used by Islamic Religious Education teachers in overcoming difficulties reading the Qur'an in grade III students at SDN 1 Kayuambon, 3) knowing the supporting and inhibiting factors experienced by Islamic Religious Education teachers in overcoming the difficulty of reading the Qur'an in grade III students of SDN 1 Kayuambon. The type of research used is qualitative research. The data sources in the study are teachers and learners. The research instruments used are observation guidelines, interview guidelines and documentation. The data analysis techniques used are data reduction techniques, data presentation and data verification. The results of the study can be as follows: 1) The role of teachers in overcoming difficulties in reading the Qur'an is not only as a guide, facilitator, and motivator but teachers also carry out learning activities by forming groups, increasing learning hours, and changing learning methods 2) Learning strategies carried out using the demonstration method, quantum teaching learning model, and contextual approach. 3) Supporting factors and inhibiting factors in overcoming the difficulty of reading the Qur'an for students of SDN 1 Kayuambon, namely supporting factors for the existence of learning facilities, parental support, and the existence of demonstration learning methods. Meanwhile, the inhibiting factors are limited time, and the lack of students in reading the Qur'an outside of school. Abstrak. Tujuan dari penelitian ini yaitu 1) mengetahui bagaimana peran guru Pendidikan Agama Islam dalam mengatasi kesulitan membaca Al-Qur’an pada peserta didik kelas III di SDN 1 Kayuambon, 2) mengetahui strategi yang digunakan guru Pendidikan Agama Islam dalam mengatasi kesulitan membaca Al-Qur’an pada peserta didik kelas III di SDN 1 Kayuambon, 3) mengetahui faktor pendukung dan penghambat yang dialami guru Pendidikan Agama Islam dalam mengatasi kesulitan membaca Al-Qur’an pada peserta didik kelas III SDN 1 Kayuambon. Jenis penelitian yang digunakan yaitu penelitian kualitatif. Sumber data dalam penelitian adalah guru pendidikan agama Islam dan peserta didik. Adapun instrumen penelitian yang digunakan yaitu pedoman observasi, pedoman wawancara dan dokumentasi. Teknik analisis data yang digunakan yaitu teknik reduksi data, penyajian data dan verifikasi data. Hasil penelitian dapat yaitu sebagai berikut: 1) Peran guru dalam mengatasi kesulitan membaca Al-Qur’an tidak hanya sebagai pembimbing, fasilitator, dan motivator tetapi guru juga melakukan kegiatan pembelajaran dengan melakukan membentuk kelompok, menambah jam pembelajaran, dan merubah metode pembelajaran 2) Strategi pembelajaran yang dilakukan yaitu dengan menggunakan metode demonsrasi, model quantum teaching learning, dan pendekatan kontekstual. 3) Faktor pendukung dan faktor penghambat dalam mengatasi kesulitan membaca Al-Qur’an siswa SDN 1 Kayuambon, yaitu faktor pendukung adanya fasilitas pembelajaran, adanya dukungan orangtua, dan adanya metode pembelajaran demonstrasi. Sedangkan faktor penghambat yaitu, adanya keterbatasan waktu, dan kurangnya peserta didik dalam membaca Al-Qur’an diluar sekolah.